Pseudopeptide polymer coating for improving biocompatibility and corrosion resistance of 316L stainless steel. Issue 119 (19th November 2015) - Liu, Songtao; Chen, Chaoshi; Chen, Lijuan; Zhu, Haikun; Zhang, Chong; Wang, Yanmei
Abstract : The coating formed by electrochemical assembly of hydrolyzed poly(2-methyl-2-oxazoline) and dopamine could improve the migration and proliferation of HUVECs. Abstract : This article described for the first time using a pseudopeptide polymer, poly(2-methyl-2-oxazoline) (PMOXA), to form a bionic non-brush coating on a 316L stainless steel surface by electrochemical assembly for improving biocompatibility and corrosion resistance. In order to produce a stable coating, dopamine (DA) and partially hydrolysed PMOXA (H-PMOXA) were used to assemble on the surfaces of the 316L stainless steel via electrochemical oxidation and a Michael addition between the multi-imino groups of H-PMOXA and poly(dopamine). The effect of the molecular weights and hydrolysis degree of PMOXA on the formed coatings with respect to the biocompatibility and corrosion resistance of the modified stent materials were studied in detail. The results showed that the coating formed by PMOXA with moderate molecular weights and hydrolysis degree possessed excellent anti-fouling properties and biocompatibility. Moreover, the migration and proliferation of Human Umbilical Vein Endothelial Cells (HUVECs) on this kind of coating were also greatly enhanced.